Dinosaurs before dark ebook - Osborne, Mary Pope (Magic Tree House, 2010)
Read the #1 bestselling chapter book that started it all! Magic. Mystery. Time-travel. Get whisked back in time in the magic tree house with Jack and Annie! Where did the tree house come from? Before Jack and Annie can find out, the mysterious tree house whisks them to the prehistoric past. Now they have to figure out how to get home. Can they do it before dark…or will they become a dinosaur’s dinner? The Magic Tree House series has been a beloved favorite for over 25 years and is sure to inspire a love of reading—and adventure—in every child who joins Jack and Annie! Did you know that there’s a Magic Tree House book for every kid? • Magic Tree House: Adventures with Jack and Annie, perfect for readers who are just beginning chapter books • Magic Tree House Graphic Novels:  Jack and Annie's original adventures come to life with full-color, vibrant art, perfect for graphic novel fans and reluctant readers • Merlin Missions: More challenging adventures for the experienced reader • Super Edition: A longer and more dangerous adventure • Fact Trackers: Nonfiction companions to your favorite Magic Tree House adventures